Government policies targeting primary care physician practice from 1998-2018 in three Canadian provinces: A jurisdictional scan. Issue 6 (June 2022) - McKay, Madeleine; Lavergne, M. Ruth; Lea, Amanda Prince; Le, Michael; Grudniewicz, Agnes; Blackie, Doug; Goldsmith, Laurie J.; Marshall, Emily Gard; Mathews, Maria; McCracken, Rita; McGrail, Kimberlyn; Wong, Sabrina; et al.
Highlights: Policy reforms across the three provinces were driven by physician payment. Policies targeted 24/7 access, team-based care, unattached patients, eHealth, and rural/Northern recruitment. Reforms were largely uniform across provinces, with Ontario's policies being most diverse. Agreements between provincial governments and provincial medical associations were highly influential. Abstract: Primary care is the foundation of health care systems around the world. Physician autonomy means that governments rely on a limited selection of levers to implement reforms in primary care delivery, and these policies may impact the practice choices, intentions, and patterns of primary care physicians. Using a systematic search strategy to capture publicly available policy documents, we conducted a scan of such policies from 1998 to 2018 in three Canadian provinces: British Columbia, Nova Scotia, and Ontario. We reviewed 388 documents and extracted 170 policies from their texts, followed by analysis of the policies' instruments, actors, and topic areas. Policy reforms across the three provinces were primarily focused on physician payment, with governments relying on both targeted incentives and reformed payment models. Policies also employed various instruments to target priority areas of practice: 24/7 access to care, team-based primary care, unattached patients, eHealth, and rural/Northern recruitment of physicians. Across the three provinces and the 20-year timespan, reform priorities and instruments were largely uniform, with Ontario's policies tending to be the most diverse. Physicians helped shape reforms through the agreements negotiated between provincial governments and medical associations, influencing the topics and timing of reforms. Future research should evaluate impacts on the delivery of primary care and explore opportunities for policy innovation.